STUDY OF THE HISTORY AND DYNAMICS OF THE AGRARIAN POLICY IN TRANSFORMING THE INDONESIA’S AGRARIAN REFORM - Rejekiningsih, Triana; Muryani, Chatarina; Lukitasari, Diana (Yustisia, 2019)
This study was conducted to find out: (1) the agrarian history as a milestone of the agrarian policy in Indonesia; (2) the dynamics of agrarian policy as a drivingfactor for the agrarian reform; (3) agrarian policy as a means of transforming theagrarian reform in Indonesia. This study is a normative juridical legal researchwith a historical approach, in addition to use conjunctural approach to examine thecomplex, historically specific, of various agrarian policies. The study concludes that:(1) Agrarian history is an important part of the agrarian policy realization, beginningfrom Dutch colonialism along with the dominated agrarian resources and the raiseof peasant resistance against imperialism, this condition gave rise to the spirit ofnational movements and the birth of Law Number 5 of 1960 on The Agrarian BasicLaw (hereinafter abbreviated to UUPA) as the basis for agrarian policy in Indonesia;(2) Not all the agrarian policies are oriented towards the objectives of the UUPA, oftentime they cause problems in their application, among others its irrelevant to principlesof justice and people's welfare, land tenure disintegration, lack of certainty over theland rights, stand for the capital owners, opening up of foreign investors controllingagrarian sources, the designation of forest areas on people’s lands, nationalization ofthe plantations, repressive resolution of agrarian conflicts, and land certification whichlegalizes inequality land tenure structures; (3) agrarian policy is an important partof the process of realizing the agrarian reform, especially in the context of agrariantransformation towards the formation of a 'agrarian' society structure integrated intoeconomic pillars to improve people’s welfare.